Design, Construction, and Laser Welding of a Contact Ring for Automated and Reliable Coil Connection for Wound Power-Dense Flat Wired Stators - Vogel, Alexander; Baader, Marcel; Wirthmann, Felix; Kühl, Alexander; Franke, Jörg; Kassel, Florian (2024 IEEE 69th Holm Conference on Electrical Contacts (HOLM), 2024)
In the manufacturing of electric motors, the stator is the most expensive component of the electric motor. For this reason, the stator is very interesting in terms of automation and offers various possibilities for increasing production efficiency. In addition to some process steps that are already highly automated, others are still largely manual. These mainly include work steps in the area of insulation assembly or contacting. In both cases, the flexible behavior of the free wire ends poses a major challenge and can only be achieved with great effort or, in the case of large quantities, by machines or robots. Especially in compact and therefore extremely power-dense drives that are not based on hairpin technology, the process of contacting the individual coils must be redesigned. To reduce the complexity of handling the free ends, the substitution of a conventional, manual crimping process through the use of a contact ring, in conjunction with a laser-assisted contacting process, can be a promising approach. This issue will be pursued as part of this scientific work and the feasibility of such geometries in interaction with laser contacting will also be demonstrated for flat wire stator
Keywords: Coils; Contacts; Welding; Production; Stators; Ring lasers; Reliability engineering; Wire; Robots; Electric motors; electric drives; stator production; contact ring; contacting; laser welding